The Role of Understory Plants in Microclimate in Coconut-Based Agroforestry - Pangemanan, Euis F.S.; Kalangi, Josephus I.; Saroinsong, Fabiola B.; Ratag, Semuel P. (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
The use of land with a coconut-based agroforestry system is currently widely practiced in the South Minahasa region. In this agroforestry system, coconut trees are planted together with other plants on a single plot of land. The diversity of underplanting also plays a role in modifying the microclimate around the coconut trees, which in turn can affect the growth and productivity of the plants. Microclimate is the climatic conditions that occur around plants and is greatly influenced by various factors, including plant diversity. Coconut trees in coconut-based agroforestry systems bring about changes in the microclimate under the canopy and can lower air temperature, reduce radiation, and decrease wind speed under the canopy. This study aims to determine the effect of various types of vegetation on the microclimate in coconut-based agroforestry. The research was conducted in Ongkaw Village using a survey method. Microclimate measurements included solar radiation transmission, air temperature, air humidity, and wind speed at each observation plot. Data on underplant vegetation was observed using a purposive sampling plot method on coconut agroforestry land with different vegetation structures. The results showed that, compared to monoculture areas, the presence of understory plants significantly reduced air temperature, increased relative humidity, slowed wind speed, and reduced the intensity of light reaching the ground. Compared to other types of plants, plots with multi-strata fruit plants had the best microclimate conditions; shrub plots showed a moderate effect on microclimate moderation, while more open plots tended to have higher temperatures and lower humidity. The conclusion of this study is that the selection of understory plants in coconut agroforestry systems greatly influences microclimate conditions. Multi-strata fruit trees have been proven to be the most effective in creating a cooler and more humid microclimate, which can contribute to improved soil health and reduced stress on the main crop